Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Join our platform to get reliable answers to your questions from a knowledgeable community of experts. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

HELP PLEASE!

can anyone help me with this math question? im quite confused on where to begin..

please explain & show the steps!


HELP PLEASE Can Anyone Help Me With This Math Question Im Quite Confused On Where To Begin Please Explain Amp Show The Steps class=

Sagot :

Answer:   -3x-2y+1

===================================================

Explanation:

In the first parenthesis grouping, we have these three terms

[tex]9x^2y[/tex]

[tex]6xy^2[/tex]

[tex]-3xy[/tex]

and we're dividing each of them over the denominator -3xy.

Think of it like the distributive property. In fact, division is a disguised version of multiplication, which is why the distributive property is not a coincidence. Example: 10/2 = 10*(1/2) = 10*0.5 = 5

If we divide each term over -3xy, then we get these three separate results:

[tex](9x^2y) \div (-3xy) = -3x[/tex]

[tex](6xy^2) \div (-3xy) = -2y[/tex]

[tex](-3xy) \div (-3xy) = 1[/tex]

The last equation is probably self explanatory: any number divided by itself is 1, as long as the number isn't zero. Eg: 4/4 = 1.

The first two equations might not be obvious. For the first equation, we divide the coefficients 9 and -3 to get -3 as the final coefficient on the right hand side. Then the variable terms cancel when pairing them up. Check out the diagram below to see what I mean by this canceling.  It's optional, but it might help to think of [tex]x^2[/tex] as [tex]x*x[/tex]

A similar situation happens in the second equation as well.

After doing those three division operations, we then add up the results to arrive at -3x+(-2y)+1 which is the same as -3x-2y+1

View image jimthompson5910